Development of liquid biphasic system for betacyanins extraction from peel and flesh of hylocereus polyrhizus and its applications - Leong, Hui Yi (2019)
In the current scenario, development of a green, simple, economically viable and effective bioseparation technology, such as liquid biphasic system, is a rapidly growing field in the biotechnology industries. Betacyanins are presently gaining higher interest in the food industries, as driven by their high tinctorial strength and healthy functional properties. In this research work, various liquid biphasic systems were utilised for the extraction of betacyanins from peel and flesh of red-purple pitaya. In particular, alcohol/salt-based liquid biphasic flotation (LBF) system and liquid biphasic partitioning system (LBPS) were first applied to the betacyanins extraction, and the satisfactory efficiencies were achieved by these approaches. With the utilisation of LBF system, the highest values of betacyanins concentration in alcohol-rich top phase (Ct) (95.989% and 95.488%), separation efficiency (E) (88.361% and 94.886%) and partition coefficient (K) (24.168 and 21.195) of betacyanins from the peel and flesh were obtained. On the other hand, the highest values of Ct (98.080% and 96.256%), phase volume ratio (Vr) (1.667 and 2.167) and K (51.097 and 25.764) of betacyanins from the peel and flesh were obtained by the application of LBPS. Subsequently, an integration of LBF system and LBPS with electricity treatment were employed for the betacyanins extraction. Electricity treatment not only ameliorates the extraction efficiency of biomolecules but also acts as a green extraction technique. Collectively, the betacyanins extraction from the peel and flesh using liquid biphasic electric flotation (LBEF) system showed the significant values of Ct (99.014% and 96.132%), E (98.383% and 96.576%) and K (100.814 and 24.883) of betacyanins compared to that of the LBF system. Similarly, the betacyanins extraction from the peel and flesh using liquid biphasic electric partitioning system (LBEPS) also demonstrated the high values of Ct (99.256% and 97.189%) and K (133.433 and 34.665) of betacyanins compared to that of the LBPS. Nevertheless, their Vr value remained the same. In addition, the peel and flesh extract obtained from these systems displayed different variations of red colour and their antioxidant properties were well retained. The 10-days stability study on the betacyanins extracted from the peel and flesh of red-purple pitaya was conducted. Our results revealed that the peel and flesh extract added with 0.5% (w/v) of ascorbic acid and without any pH adjustments showed a good stability of betacyanins under different storage conditions. Especially, the retention of betacyanins’ activity in peel and flesh extract at 4 °C dark storage were the highest (114.976% and 105.903%). Lastly, two different applications were successfully accomplished in the present study. The salt-rich waste feedstock obtained from the liquid biphasic systems was used in the Aurantiochytrium limacinum SR21 wild type cultivation, and a higher lipid accumulation (8.29%) and docosahexaenoic acid (DHA) production (128.81 mg.L-1) were noted. Whereas, the natural plant pigment products containing the stabilised betacyanins were applied as the natural red colourants for hard candy production. To conclude, this dissertation presents the reliable and effective separation approaches for the extraction of biomolecules like betacyanins valuable for food processing. In addition, this study shows a responsible practice on waste management.